Smoking as a Risk Factor for Arrhythmia in Cengkareng General Hospital, Jakarta, Indonesia, during 2020-2024 - Princyelova Estevan Sutantyo; Andria Priyana (Universitas Airlangga, 2026)
Highlights: No significant association was found between smoking habits and arrhythmia, despite a slightly elevated prevalence ratio. Ventricular extrasystole constituted the predominant subtype of arrhythmia observed in the study population. Abstract Introduction: Arrhythmia is a cardiac rhythm disorder associated with stroke, heart failure, and sudden death. Smoking is an established cardiovascular risk factor, yet its relationship with arrhythmia remains insufficiently explored in Indonesia. This study aimed to examine the association between smoking habits and arrhythmia among patients at Cengkareng General Hospital, Jakarta, Indonesia. Methods: A cross-sectional study was conducted at Cengkareng General Hospital, Jakarta, Indonesia, including 140 patients aged ≥18 years old diagnosed with arrhythmia. Data were analyzed using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 25.0. Results: Of all participants, 59.3% were males and 20.7% were smokers. Arrhythmia was detected in 95.7% of cases, with ventricular extrasystole (VES) being most frequent (65%). Statistical analysis demonstrated no significant association between smoking and arrhythmia, although smokers exhibited a marginally higher risk (probability/Pr=1.011). Hypertension, diabetes mellitus (DM), renal dysfunction, and medication use were also identified as contributing factors. Conclusion: Although smoking was not significantly associated with arrhythmia, it showed a tendency to increase risk. Ventricular extrasystole was the predominant arrhythmia observed in this cohort.